More than meets the eye ; Save the chapel ; Balicasag [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Interview with Ka Roger, NPA Melito Glor Command Spokesman about graft and corruption raps against Ka Hector. Twenty years after businessman John Gokongwei bought a Jesuit owned real estate property in Ermita, he is finally claiming it for commercial purposes. The Probe Team takes a break in the newed diving haven off the Southeastern tip of Bohol.
More than meets the eye (20 min.) -- Save the chapel (12 min.) -- Balicasag (17 min.)
VHS
Keywords: New People's Army; Saint Thomas Moore Chapel (Ermita, Manila); Communists -- Interviews. -- Philippines; Balicasag Island (Bohol).